2012
DOI: 10.1111/j.1467-8268.2011.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Nigerian Agricultural Efficiency Literature, 1999–2011: What Does One Learn from Frontier Studies?

Abstract: The objective of the study is to provide a critical overview of Nigerian agricultural efficiency literature covering 1999–2011. A total of 156 frontier studies which yields 210 observations were used for the review. The preliminary findings from both the Funnel Plot and Funnel Asymmetry Test revealed that publication bias is not a severe problem in the selected literature. Our findings via univariate scatter plot and Spearman correlation provided evidence that reported efficiency scores positively correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
3
13
0
1
Order By: Relevance
“…The coefficient of CDF is positive and statistically significant, suggesting that the less adjustable functional form (Cobb-Douglass) tends to yield higher MTE estimates than the more flexible Translog). This finding is in conformity with the result of Ogundari et al (2012), but contradicts two out of three models studied by Bravo-Ureta et al (2007) and all of the studies of Ahmad and BravoUreta (1996), Resti (2000), and Thiam (2003). Sample size had no statistically significant effect on MTE, but VARS (number of independent variables) had a positive and statistically significant effect, implying that studies with many independent variables tend to yield higher MTE estimates.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The coefficient of CDF is positive and statistically significant, suggesting that the less adjustable functional form (Cobb-Douglass) tends to yield higher MTE estimates than the more flexible Translog). This finding is in conformity with the result of Ogundari et al (2012), but contradicts two out of three models studied by Bravo-Ureta et al (2007) and all of the studies of Ahmad and BravoUreta (1996), Resti (2000), and Thiam (2003). Sample size had no statistically significant effect on MTE, but VARS (number of independent variables) had a positive and statistically significant effect, implying that studies with many independent variables tend to yield higher MTE estimates.…”
Section: Resultssupporting
confidence: 76%
“…Nevertheless, empirical studies in agriculture have shown that technical efficiency scores were seriously affected by the choice of estimation technique (Thiam et al 2001;Bravo-Ureta et al 2007;Ogundari et al 2012). To our knowledge, there has been no meta-analysis of technical efficiency in aquaculture to guide planners and investors.…”
Section: Introductionmentioning
confidence: 99%
“…() who found that extension services increase TE in rice production. Ogundari et al (), based on Nigerian literature, argued that increased extension‐technology management has the potential to drive efficiency and can be a stimulus for agricultural growth.…”
Section: Resultsmentioning
confidence: 99%
“…The stochastic production frontier model by Parikh and Shah (1994), which in turn derives from the composed error model of Aigner, Lovell, and Schmidt (1977), Meeusen and van den Broeck (1977) and Forsund, Knox Lovell, and Peter (1980), was used to examine the impact of cassava-processing technologies on farmers' efficiency in cassava production, following similar efficiency studies by Fakayode et al (2008), Ogundari, Amos, and Okoruwa (2012) and Girei et al 2014). This was done by comparing the efficiency measures of farmers that are located in mechanized-processing villages with farmers in nonmechanized villages.…”
Section: The Stochastic Frontier Model For Uganda Cassava Farmersmentioning
confidence: 99%